ANALYSIS AND PROPOSED IMPROVEMENT OF PROCUREMENT STRATEGY IMPLEMENTATION OF PT. KRAKATAU STEEL (PERSERO) Tbk. - RUSTANDI LEMAN (NIM: 29110423) Pembimbing : Ir. Gatot Yudoko, MA.Sc, Ph.D., ANDI
Accelerated changing in business environment and global economic causing problems and disturbance in raw material supply for steel industry. Global steel industry has been facing overcapacity which causes the shortage and instability of raw material supply for steel industry production lines. To ensure the availability of raw materials, steel producer should be able to anticipate the risk and complexity in raw material procurement globally. PT Krakatau Steel (Persero) Tbk as one of the biggest steel producer in Indonesia and South East Asia is also experiencing the same problem. In anticipating the threat of uncertainties in supply and high price of raw material, the company needs a procurement strategy that can give direction to carry out the procurement process effectively and efficiently. Currently, the company does not have a reliable procurement strategy to cope with such threats, due to the lack of methods that can be used to classify materials as well as defining the procurement strategy. Kraljic purchasing portfolio approach seems to fit the current needs of the company. This approach is portfolio matrix approach that classifies products in two basic dimensions which then produces a 2x2 matrix with classification into 4 categories. With the help of this matrix, the company will carry out the classification of various items of material and choosing the right strategy for each category The result of this study is PT Krakatau Steel (Persero) Tbk procurement portfolio matrix which is formed from 2 dimensional procurement, i.e.: procurement value and procurement risk. This matrix classifies all of 37 group of materials into 4 quadrants: Non-critical (14 group materials), Bottleneck (4 group materials), Leverage (6 group materials), and Strategic (13 group materials). From each quadrant then we can define the corresponding strategic action to be taken, totality they are 10 different strategic action definition for company procurement process. Evaluation on each strategic actions then compiled to an application plan for each group materials in daily operation. With these results the company can improve the implementation of corporate procurement strategy in supporting the achievement of corporate objectives. From this matrix, it could be seen that PT. Krakatau Steel (Persero) Tbk. faces high procurement risk for most of its procurement due to the limitation of import resources and the limitation number of suppliers.Implementation of the procurement strategy should start from a determination of the procurement policy that sets out overall direction for procurement process. It is necessary to carry out the socialization process to related parties from operational level up to decision makers, followed by the formation of the whole team for the preparation of procedures and infrastructure.